The Al Qaeda brand: the strategic use of the “terrorist” label - Pokalova, Elena (Terrorism and political violence, 2018)
Al Qaeda leaders have consistently praised the Chechen insurgents as an exemplary front of global jihad. Ayman al-Zawahiri recently applauded the steadfastness of the Chechen rebels and indicated that their resolve for jihad is worthy of emulation. Ever since the world found out about a war going on in the Muslim republic in the North Caucasus, Al Qaeda leadership has attempted to represent the Chechen struggle as one of its own battlefields. In turn, the Russian government has tried to justify its policies in the North Caucasus through demonstrating to the world that the Kremlin is fighting nothing less than Osama bin Laden’s agents in Chechnya. The North Caucasus insurgents in turn have embraced some of Al Qaeda’s narratives. While such narratives have proliferated, the factual evidence to show the direct links between the North Caucasus insurgents and Al Qaeda is still lacking. The article examines how terrorist groups such as Al Qaeda use framing for strategic ends. The evidence discussed here suggests that Al Qaeda, the North Caucasus insurgents, and the Russian government have adopted similar narratives. However, the lack of evidence to back up such narratives indicates the differences in reasons driving the convergence of the narratives.